Investigating the Influences of Automated Guided Vehicles (AGVs) as Material Transportation for Automotive Assembly Process / Seha Saffar...[et al.] - Saffar, Seha; Jamaludin, Zamberi; Jafar, Fairul Azni (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Optimizing material handling system adds to the performance level of the manufacturing process and at the same time avoid waste of time and cost. A case study at one of automotive manufacturing industry, focusing on observing the material flow between warehouse and assembly shop are done and the result showed the work is manually done. It's caused a longer time in handling the material and risk in damaging parts. Thus, a work presented in this paper is based on real industry situation, with the purpose of investigating the influences of AGV's application in the automotive assembly process. AGV (material transportation) and Pick-To-Light system (part supply system) are used as variable to improve the current case study performance. But in this paper, the result of comparison between transportation is discussed, focusing on the influences of AGV only. A method of discrete-event simulation using Delmia/Quest software was introduced. 2 models for each type of transportation is made in Quest with a very similar assembly process from the real situation in automotive industry and the result is compared to see the influenced of the AGV to the system performance. Based on the comparison, the part supply in the assembly process increase by 70% from its current state. Meanwhile, transportation idle time reduce by 26% and part waiting time at warehouse reduce at most 85%. Thus, transportation utilized more into 30% by applying AGV as material transportation. From the improvement made shows the influence of AGV in case study company as well as manufacturing industry.